The Principle of Convenience in Islamic Sharia: An Analysis of the Rules of Al-Masyaqqah Tajlibut Taysir - Aga Setiawan; Sonya Noprisa Sumantri (ISNU Nine-Star Multidisciplinary Journal, 2025)
Leniency (rukhsah) in carrying out Islamic sharia is a form of convenience given by Allah SWT to His people, as enshrined in the rules of fiqh "al-masyaqqah tajlibut taysir". This rule is an important foundation in facing various challenges and dynamics of modern life that often cause difficulties. This study aims to analyze the application of the rules of al-masyaqqah tajlibut taysir in the context of contemporary worship and muama. The research method used is library research with a normative-philosophical approach. The research stages include collecting data from primary and secondary literature, identifying basic concepts and principles, and analyzing relevant contemporary cases. The results of the study show that the rules of al-masyaqqah tajlibut taysir have strong relevance in providing sharia solutions to new problems, such as prayer relief for night shift workers, the determination of fasting times for travelers on planes, or the flexibility of digital financial transactions. The application of this rule requires a deep understanding of the maqashid sharia (sharia goals) and uruf (customs) of society. Further discussions highlighted the importance of collective ijtihad in interpreting and applying these rules so that there is no abuse or liberalization of sharia. This research is expected to contribute to the development of contemporary fiqh that is responsive to the changing times without ignoring the basic principles of sharia.